2010
DOI: 10.3329/jsr.v2i2.4159
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Yeasts from Various Food Products and Detection of Killer Toxin Activity <i>In vitro</i>

Abstract: Yeasts produce killer toxin, which gives them a selective advantage against susceptible yeasts. In this study we isolated 8 various non-pathogenic yeasts from 12 different food products and detected killer toxin activity in them against a clinical isolate of Cryptococcus neoformans by chloroform exposure method. The experiment was performed in two sets that had 3 replicates each. The first set plates and the second set plates were exposed to chloroform once and twice respectively. Among the 8 yeasts, 5 yeasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Vitamins play key role in numerous metabolic processes of the body and yeasts have been reported to be able to produce vitamins, especially vitamin B complex, which is a distinctive advantage for yeast to be used as a probiotic over bacteria [52]. Dubash et al [53] reported a number of yeast strains belonging to Sachharomyces cerevisiae, Candida pintolopesii, Candida tropicalis, Pichia anomala and Dekkera spp. with killer toxin activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamins play key role in numerous metabolic processes of the body and yeasts have been reported to be able to produce vitamins, especially vitamin B complex, which is a distinctive advantage for yeast to be used as a probiotic over bacteria [52]. Dubash et al [53] reported a number of yeast strains belonging to Sachharomyces cerevisiae, Candida pintolopesii, Candida tropicalis, Pichia anomala and Dekkera spp. with killer toxin activity.…”
Section: Discussionmentioning
confidence: 99%
“…The isolate don’t produce gelatinase and DNase indicating its safety to be used for human patients as most of the pathogenic microorganisms produce these enzymes as part of their pathogenesis [26]. Cholesterol assimilation by yeast with probiotic attributes has also been reported by Chen et al [53]. Syal and Vohra [26] reported yeast isolates that showed high auto-aggregation ability and cell surface hydrophobicity.…”
Section: Discussionmentioning
confidence: 99%
“…It must be taken into consideration that Candida is not only highly widespread in the human body but it is also the main genus of yeasts which contaminate foods [40], being C. albicans, C. parapsilosis, C. tropicalis, C. glabrata and C. rusei the main pathogenic species [41]. The first three of them have been frequently isolated from foods such as milk, cheese, juices and salads [42,43]. Regarding intra-yeast H. pylori detection in foods, it has been reported within yeasts species of Candida isolated from different food sources, such as yogurt, grape juice, bread, preserves, fruits and honey [30,39].…”
Section: Helicobacter Pylori and Its Relationship With Candida Spmentioning
confidence: 99%
“…For primary testing, filtered or concentrated supernatant samples were dropped (10, 25, 50 lL) on plates with a 0 1 strain, and the formation of lysis zones was observed after 4 days of the incubation at 18-20°C. Concentrated proteins were analysed using SDS-PAGE method [25].…”
Section: Isolation Of Yeast Killer Toxins and Protein Electrophoresismentioning
confidence: 99%